Música, juventude, comportamento: nos embalos do Rock n Roll e da Jovem Guarda (Uberlândia , 1955-1968) - Silva, Elmiro Lopes da (2007)
The thematic of quarrel in this work is the relation between music and youth, initiate with the sprouting of Rock' n' Roll in the United States, in the decade of 1950, and that world was become enlarged measures, receiving in Brazil the denomination of Jovem Guarda, in sixties years. The first chapter focuses the origins of Rock' n' Roll, with intention to point the elements that defined it as a new musical and mannering language of young identification, arriving until the sprouting of the Jovem Guarda, as movement of identification of a parcel of Brazilian youth. We used diverse depositions on these times, of pioneering artists and young constituent of that public, the recording production (records, musics, graphical material), beyond informative biographies, texts, among others. In the following chapter, we focus over the first repercussions of young music in the city of Uberlândia (MG). In this way, we dedicate attention for its penetration in the radio environment, initiate still in the years of 1950; we analyze critical to it directed by the local newspaper Correio de Uberlândia and the searching to the youngs that had adhered to the behavior spread out for artists as The Beatles and Roberto Carlos (the long hair ). We work with the discographic collection Geraldo Motta Baptista (CDHIS/UFU), beyond some verbal depositions and of the publications/chronics/notes of the related newspaper, published between 1955 and throughout the decade of 1960. The final chapter focuses the function role played for programmings of television, commercial spaces of sociability and establishments in the diffusion of young music in local society respectively represented by the program Clube do Guri (TV Triângulo), Uberlândia Clube and the record store A Discolândia. By this way, we search to explore experiences lived for cultural promoters, people of the radio and the TV, admirers of artists and record consumers, as well as of the local artists called of Nossa Jovem Guarda .